Pelatihan Digital Marketing Untuk Meningkatkan Potensi Wisata Kampung Coklat Majapahit Di Kecamatan Dlanggu Kota Mojokerto: indonesia - tegowati stiesia; In’am Widiarma; Yayah Atmajawati (Jurnal Penamas Adi Buana, 2021)
Cocoa is one of Mojokerto regency's mainstay commodities and has been developed in 2010 in 12 sub-districts and making the Dlanggu sub-district a development center. In developing cocoa, farmers need financing, increased knowledge related to cocoa plant pest prevention, product packaging and online marketing. So the Financial Services Authority (OJK) together the East Java Provincial Plantation Service & East Java BPR who are members of the East Java Province Regional Financial Access Acceleration Team (East Java TPAKD) held a "Business Matching Acceleration of Financial Access and Training, Financial Literacy and Inclusion (PETIK)" to 100 Cocoa farmers in Mojokerto to increase the quantity of cocoa production through providing credit facilities for cocoa farmer groups & improving cocoa quality through training in cocoa pest management, product packaging and online marketing. This PKM (which is part of an event organized by the TPAKD East Java aims to provide online marketing knowledge for Mojokerto cocoa farmers. With online marketing training, cocoa farmers have understood the benefits and how to properly apply online marketing. It is hoped that Mojokerto chocolate tourism will be better known so that there will be more visitors and can generate greater income from the tourism potential of the chocolate village.